The role of interaction between social organizations and specialized medical centers in the treatment of children with inborn cleft lip and palate - A. A. Mamedov; O. V. Nelyubina; M. A. Abiev (Сеченовский вестник, 2011)
The aim of this research is to propose an algorithm for complex rehabilitation of children with congenital cleft lip and palate. We have 35 years of experience working with children with congenital cleft lip and palate, evidence-based approach to strategy and tactics of treatment of such children. The main purpose of the proposed algorithm for treatment of children with congenital cleft lip and palate is an early rehabilitation with early restoration of the anatomy and function of maxillofacial organs.